The prevention of thermal losses from automotive lubricants to improve cold start efficiency - Roberts, Andrew P. (2015)
The internal combustion (I.C.) engine remains unrivalled as the primary means of road vehicle propulsion. The frequency of re-fuelling stations, combined with the high energy density of both gasoline and diesel fuel provide users with unrivalled flexibility and vehicle range. However a range of environmental and health concerns exist surrounding I.C. engine emissions; in particular carbon dioxide (CO2), nitrous oxides (NOx), hydrocarbons (HC) and carbon monoxide (CO). There is therefore increasing pressure on vehicle OEMs to reduce vehicle emissions through tightened emission standards and regulations. A significant challenge in meeting these tightened regulations is the reduced efficiency of the I.C. engine during cold-start which reduces from typical values of 40% when fully warm to values as low as 10% when cold. Increased friction in the engine caused by overly viscous lubricants providing sub-optimal lubrication during cold starts is a primary cause of this reduction in efficiency during cold-start. This is despite the advancements in lubricant technology made that has reduced the sensitivity of lubricant viscosity to temperature variation.